Regnase-1 and Roquin Nonredundantly Regulate Th1 Differentiation Causing Cardiac Inflammation and Fibrosis - Cui, Xiaotong; Mino, Takashi; Yoshinaga, Masanori; Nakatsuka, Yoshinari; Hia, Fabian; Yamasoba, Daichi; Tsujimura, Tohru; Tomonaga, Keizo; Suzuki, Yutaka; Uehata, Takuya; Takeuchi, Osamu (The Journal of immunology (1950), 2017)
Regnase-1 and Roquin are RNA binding proteins that are essential for degradation of inflammatory mRNAs and maintenance of immune homeostasis. Although deficiency of either of the proteins leads to enhanced T cell activation, their functional relationship in T cells has yet to be clarified because of lethality upon mutation of both Regnase-1 and Roquin. By using a Regnase-1 conditional allele, we show that mutations of both Regnase-1 and Roquin in T cells leads to massive lymphocyte activation. In contrast, mutation of either Regnase-1 or Roquin affected T cell activation to a lesser extent than the double mutation, indicating that Regnase-1 and Roquin function nonredundantly in T cells. Interestingly, Regnase-1 and Roquin double-mutant mice suffered from severe inflammation and early formation of fibrosis, especially in the heart, along with the increased expression of , but not or Consistently, mutation of both Regnase-1 and Roquin leads to a huge increase in the Th1, but not the Th2 or Th17, population in spleens compared with T cells with a single Regnase-1 or Roquin deficiency. Regnase-1 and Roquin are capable of repressing the expression of a group of mRNAs encoding factors involved in Th1 differentiation, such as and , via their 3' untranslated regions. Moreover, Regnase-1 is capable of repressing Roquin mRNA. This cross-regulation may contribute to the synergistic control of T cell activation/polarization. Collectively, our results demonstrate that Regnase-1 and Roquin maintain T cell immune homeostasis and regulate Th1 polarization synergistically.